The Bacterial and Viral Communities Associated with Onion Bacterial Bulb Rot - Christopher Liakos; Verushka Ibanez; Pedro H. Lebre; Mike L. Derie; Jacquie van der Waals; Lindsey du Toit; Bhabesh Dutta; Brian Kvitko; Don A. Cowan; Teresa A. Coutinho (Phytobiomes Journal)
Microbes occur in complex communities within plants as endophytes and establish a network of interactions that can influence plant health positively or negatively. Positive interactions may be synergistic and confer abiotic and biotic stress tolerance. The aim of this study was to identify bacteria and viruses present in storage onion bulbs that were symptomatic and asymptomatic for bacterial bulb rot from crops grown in Georgia and Washington states, and to assess their potential role in the bulbs based on the functions of bacterial and viral genes detected. DNA was extracted from nine asymptomatic bulbs and nine bulbs displaying symptoms of bacterial bulb rot and subjected to 16S rRNA amplicon sequencing and metagenome-assembled genome analysis. The Illumina platform was used to sequence the hypervariable region (V3-V4) of the 16S rRNA gene. The 16S rRNA amplicon profiling revealed the presence of numerous bacteria, including potential onion pathogens in the genera Pantoea and Burkholderia. Metagenome-assembled genome assembly identified P. agglomerans, B. gladioli, and B. cepacia, known bulb rot pathogens, including genes linked to fitness and those involved in both type II and III secretion systems. Eighty-nine unique viral genomes were identified, of which 67 could be classified taxonomically. The bacterial and viral genomes differed significantly in asymptomatic versus symptomatic bulbs. Viral genomes showed evidence of auxiliary metabolic genes, including genes involved in fitness and pathogenicity to bacterial hosts. The onion bulbs hosted endophytic bacteria and viruses, some of which were potentially beneficial and others potentially pathogenic to onion or as hosts to bacteriophages. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.